Skin, but not gut, microbial communities vary with social density in Antarctic fur seals - Petroula Botsidou; Petroula Botsidou; Michael Schloter; Michael Schloter; Öncü Maraci; Silvia Gschwendtner; Rebecca Nagel; Rebecca Nagel; Jaume Forcada; Joseph I. Hoffman; Joseph I. Hoffman; Joseph I. Hoffman; et al. (Frontiers in Microbiology)
Comparative studies of microbial communities occupying different body sites in wild vertebrates are scarce, but they are crucial for advancing our understanding of the ecological and evolutionary factors shaping animal microbiomes. We therefore used a natural experiment comprising mother-offspring pairs from two adjacent Antarctic fur seal breeding colonies that differ in social density to investigate differences between skin and gut microbial communities in relation to host-specific and environmental factors. Using 16S rRNA amplicon sequencing, we uncovered a strong influence of colony on the diversity and composition of skin but not gut microbial communities. Specifically, we observed a suppressive effect of high social density on skin microbial alpha diversity as well as an overabundance of phyla associated with diseases and bite wounds in the high-density colony. Our findings suggest that skin microbial communities may be more sensitive to external factors, whereas gut communities are more tightly regulated by the host. Overall, this study highlights the importance of considering multiple body sites and their distinct microbial communities to develop a more comprehensive understanding of the factors shaping microbial diversity and composition in marine mammals.